A practical guide to teaching physical education in the secondary school - Capel, Susan Anne, 1953-; Breckon, Peter, 1948- (Milton Park, Abingdon, Oxon : Routledge, 2013)
'This practical and accessible workbook is designed to support physical education student teachers as they develop their basic teaching skills, and increase their broader knowledge and understanding for teaching physical education. A Practical Guide to Teaching Physical Education in the Secondary School provides a wealth of practical activities and materials, underpinned by relevant evidence/theory, designed to support student physical education teachers' learning: - case studies, examples of pupils' work, examples of existing good practice and a range of tried and tested strategies will support student teachers in their development - an annotated reference and resources section will give advice about selection of resources on the web and elsewhere - photocopiable resources and training materials, also available to download from the Routledge website, offer easy assistance in lesson planning and preparation'--
Includes bibliographical references and index.
Keywords: Physical education and training -- Study and teaching (Secondary).; Physical education and training -- Curricula